Mungbean G × E interaction unveiling resistance to Cercospora leaf spot through GGE biplot analysis - Mohammad Irfan; Mohd Ashraf Bhat; Uzma Rashid; Farooq Ahmed Bhat; Khairiah Mubarak Alwutayd (Scientific Reports)
Abstract Cercospora leaf spot (CLS), caused by Cercospora canescens, is a major threat to mungbean production worldwide. The disease is complicated by its wide host range, diverse pathogenic strains, and the influence of environmental factors. Understanding the interplay between the host, pathogen, and environmental conditions is crucial for developing effective control measures. In a bid to identify and validate CLS resistant mungbean genotypes we conducted multi-environment trials; Genomic selection of mungbean for resistance against CLS necessitates pre-identification in diverse environments. Initially, 110 genotypes were screened under controlled conditions in which thirty-day-old mungbean plants were thoroughly sprayed with the spore suspension using a glass atomizer. After three weeks of revalidation under controlled conditions, Koch’s postulates was adopted for disease identification before selecting 16 genotypes for field testing across four different environments over three successive years. The results obtained from the GGE biplot analysis emphasize the importance of taking both genetic and ambient factors in consideration when evaluating the potential of mungbean genotypes for resistance against CLS and therefore two genotypes “SK-89 (15)” and “WMB-9 (14)” was identified as desirable genotypes. The Additive Main Effects and Multiplicative Interaction (AMMI) model and the GGE biplot have emerged as potent tools for unraveling GEI complexities. It has expanded its application to include evaluation of resistant genotypes and to locate “ideal” evaluation sites and “mega environments” linked to resistance against infection. The study provides valuable insights for future breeding programs, allowing researchers to focus on incorporating these resistant traits into future varieties.